Tailoring the structure-morphology-vibrational-optical-dielectric and electrical characteristics of Ce@NiO NPs produced by facile combustion route for optoelectronics. (May 2021) - Shkir, Mohd; Chandekar, Kamlesh V.; Khan, Aslam; Alshahrani, T.; Mohamed El-Toni, Ahmed; Sayed, M.A.; Singh, A.K.; Ansari, Anees A.; Muthumareeswaran, M.R.; Aldalbahi, Ali; Gupta, Ravindra Kumar; AlFaify, S.
Abstract: Nickel oxide is found to have a wide-range of applications in opto-electronic fields. So, we have synthesized the NiO with 0, 1, 2.5, 5 and 7.5 wt% Ce ion through one pot flash combustion route facilely at 450 °C and subjected to various state of art-excremental studies. Structural study points out that the major phase is belongs to cubic NiO, however, low intensity peaks were observed for cubic CeO2 as well. Hence, it confirms the Ce doping in NiO. This was further confirmed from FT-Raman spectroscopy analysis in which the extra vibrational mode at 450 ± 5 is belongs to Ce2 O at higher content of Ce. Further confirmation of Ce presence and its homogeneity in the final product was approved through energy dispersive X-ray spectroscopy/e-mapping measurements. The morphological investigation was done by SEM and Field emission-SEM which confirm the formation of low dimension nanoparticles of size within the range of 41–75 nm. Diffused reflectance spectra were used to obtain energy gap using Kubelka-Munk relation and noticed in range of 3.42–3.55 eV for NiO@Ce NPs. Frequency dependent dielectric and electrical properties were also studied and discussed in detail. Highlights: Facile synthesis of high purity Ce@NiO NPs was achieved by flash combustion process. XRD and FT-Raman spectroscopic studies confirm the cubic structure of Ce@NiO NPs. Crystallite size increased from 17 to 26 nm with Ce doping in NiO. Reduction in energy gap from 3.54 to 3.43 eV was noticed by Ce doping in NiO. High dielectric constant and electrical conductivity was noticed in Ce@NiO NPs.